Kebijakan Pidana Perdagangan Organ Tubuh Manusia di Indonesia yang Adil dan Ideal - M. Fadli Saputra (Jurnal Jejak Hukum Indonesia (JHI), 2025)
The people's need for methods of treating or curing diseases through organ and/or tissue transplantation shows quite significant dynamics. However, these community needs are not balanced with comprehensive legal regulations so as to provide optimal legal protection for the implementation of organ and/or human tissue transplants in Indonesia. This scientific work uses descriptive methods with a normative approach. This scientific work explains that positive law in Indonesia has formulated and regulated organ transplantation and includes prohibitions on commercial or buying and selling or exploitation of body organs in various regulations, but has not clearly regulated what can and cannot be done in obtaining body organs for transplantation to maintain a person's survival.